(untitled) (LEARNing Landscapes, 2023)
In this article the authors, a Mathematics education professor and two English education professors, describe how we used poetic inquiry in peer-led professional development workshops for field supervisors, who observe and evaluate teacher candidates. Poetic inquiry was taken up to better understand our shared experiences of mentoring teacher candidates and to deepen our thinking about our own pedagogical practices. The experience of writing and sharing these poems in our monthly workshops highlighted commonalities in our values and approaches to mentoring teacher candidates and allowed us to reflect on our own identities and how they influence our practices.